Discovery Learning: Meningkatkan Keterampilan Kolaborasi dan Komunikasi Matematis Siswa dalam Pembelajaran Matematika - Baiti, Elisa Nur; Nurmadina, Nurmadina; Novitasari, Dini; Nurjanah, Nurjanah (Jurnal Didaktika Pendidikan Dasar, 2025)
Collaboration and communication skills are part of the 21st century competencies needed to face technological developments and globalization. Discovery Learning model is one of the alternatives in improving students’ collaboration and communication. This study was conducted to analyze the effect of Discovery Learning model on students’ mathematical collaboration and communication skills in mathematics learning. This study used Systematic Literature Review (SLR) method with PRISMA protocol to evaluate relevant articles through Scopus and Google Scholar database. From the process of 112 articles that were netted, there were 6 articles that met the criteria for further review. The results showed that Discovery Learning effectively improved students’ communication skills, including the ability to convey ideas orally, in writing, and using mathematical notation. In addition, this model also improves students’ collaboration skills in terms of responsibility, flexibility, cooperation, and group interaction. With a structured approach through stages such as stimulus, data collection, and generalization, Discovery Learning promotes active, meaningful, and interactive learning. The findings recommend the implementation of Discovery Learning to support mathematics learning that is relevant to the challenges of the modern era.